Elasticity of substitution between clean and dirty energy inputs: A macroeconomic perspective - Chris Papageorgiou; Marianne Saam; Patrick Schulte (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
Recently Acemolgu, Aghion, Bursztyn and Hemous (AER 2012) formulated a model in which a high macroeconomic elasticity of substitution between clean and dirty production represents a crucial condition for green growth. Until now it has never been systematically estimated. Using a novel panel of cross-country sectoral data, we formulate specifications of nested CES production functions that allow to estimate a special case of this parameter: the elasticity of substitution between clean and dirty energy inputs. Contrary to what is expected based on the earlier interfuel substitution literature, we find evidence that this elasticity exceeds one.
urn:nbn:de:bsz:180-madoc-352093
Keywords: O44; O47; Q54; Q58; 330; clean and dirty energy inputs; aggregate elasticity of substitution; CES function; cross-country sectoral data; environmental policy